Impacts of oyster farms on sediment-associated mercury and methylmercury concentrations and health risks in an estuarine, mangrove forest, Zhanjiang Bay, China - Zhao, Zike; Chen, Chunliang; Feng, Mengqian (Frontiers in Marine Science, 2024)
The release of mercury (Hg) in response to human activities raises concerns about its potential ecological and human health effects. Hg cycling by measuring the concentrations of, and controls on, the spatial distribution of total Hg (THg) and methylmercury (MeHg) in high-tidal zone (HTZ) and mid-tidal zone (MTZ) sediments of a mangrove forest (MF) and oyster farm (OF) was examined in northwestern Zhanjiang Bay. Concentrations of both THg and MeHg ranged between 20.0-104.0 ng/g and 0.011-0.277 ng/g in the sediments, respectively. The highest methylation potentials within the MF and OF were in sediments located approximately 10-15 cm below the surface. MeHg in the HTZ of the OF was likely derived from exogenous inputs as Hg methylation appears limited. A risk assessment of MeHg during the anthropogenic disturbance of this estuaries conducted on individuals eating oysters demonstrated that health risks are low.